The clean energy-growth nexus with co2 emissions and technological innovation in Norway and New Zealand - Fei, Q.; Rasiah, R.; Shen, L.J. (Multi-Science Publ Co Ltd, 2014)
This study revisits the energy-growth nexus by incorporating the effect of clean energy, CO2 emissions and technological innovation within the research background of Norway and New Zealand over the period from 1971 to 2010. The result of the autoregressive distributed lag model indicates that there is long-run equilibrium among clean energy, economic growth, CO2 emissions and technological innovation for both countries. The result of the Granger causality test suggests that the use of clean energy does assuage CO2 emissions at the expense of economic growth. As the majority of countries are supposed to participate in the pace of environmental protection, examining Norway and New Zealand provides readers an insight of the double edge effect of clean energy on CO2 emissions and economic growth. It is worth to mention that the endogenous growth theory plays an effective role in the energy-growth nexus. To optimize the benefits of clean energy use, Norway and New Zealand should pay attention to their research and development processes.